Judaica Europeana: An Infrastructure for Aggregating Jewish Content - Winer, Dov (Judaica Librarianship, 2014)
Judaica Europeana envisions a world in which all digitized Jewish content in a variety of databases worldwide is aggregated and made accessible to users and applications anywhere, at any time. It seeks to set the ground so such content is cross-linked to conceptual structures (vocabularies, encyclopedias) that enrich them and provide contextual significance. Judaica Europeana is part of a cluster of projects building Europeana, a Linked Data infrastructure initiative of the European Commission. Judaica Europeana involves now some thirty-five partners from Europe, America and Israel, among them some of the most important Jewish content holders running long term digitization programs. It aggregated more than five million digital cultural objects and is continuing to process more. The data model (EDM) for describing these contents is that adopted by both leading world initiatives, Europeana and the Digital Public Library of America. The basic approach enabling EDM and based on the application of protocols and standards like RDF and Linked Data is surveyed and some actual examples of their current applications provided. The critical role of vocabularies for conceptual integration and access to contents is reviewed. A work program is outlined for the use of such vocabularies (thesauri, taxonomies, encyclopedias, etc.) to enrich the digitized content, interlink its diverse manifestations, and provide context and meaning. A first substantial achievement in carrying out such program is the publication of the YIVO Encyclopedia of Jews in Eastern Europe as Linked Data. Two main challenges facing the domain in the near future are detailed: (1) How to expand the availability, reaching a critical mass, of Jewish related vocabularies supporting queries like Who? What? When? Where? and expressed in the Linked Data/SKOS formats. (2) How the solid bases of such infrastructure so established may have an enabling effect in the development of new services: sophisticated offerings to the patrons of websites/portals, advanced K-12 ICT-based education, mobile cultural tourism applications, e-books, digital narratives storytelling, digital humanities scholarship, virtual research environments, MOOCs.